2007
DOI: 10.1037/0021-843x.116.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-system fit in couples: Emotion regulation when one or both partners smoke.

Abstract: In a laboratory smoking experiment, 25 couples in which 1 or both partners continued to smoke despite 1 of them having heart or lung disease discussed a health-related disagreement before and during a period of smoking. Immediately afterward, the partners used independent joysticks to recall their continuous emotional experience during the interaction while watching themselves on video. Participants in dual-smoker couples reported increased positive emotion contingent upon lighting up, whereas those in single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 33 publications
(34 reference statements)
3
63
1
Order By: Relevance
“…The pattern of an unhealthy behavior in some way benefitting the couple has been described in the literature as symptom-system fit (SSF; Rohrbaugh, Shoham, & Racioppo, 2002). For instance, Shoham et al (2007) showed that couples in which both partners smoked reported an increase in positive emotion when they were asked to smoke together in a laboratory setting, whereas those in single-smoker couples reported a decrease in positive emotion. Similarly, dual-smoker couples demonstrated an increase in emotional synchrony and engagement with each other, whereas single-smoker couples demonstrated the opposite (Butler, Hollenstein, Shoham, & Rohrbaugh, in press;Rohrbaugh et al, 2009).…”
Section: Eating To Regulate Emotions In Couplesmentioning
confidence: 95%
See 1 more Smart Citation
“…The pattern of an unhealthy behavior in some way benefitting the couple has been described in the literature as symptom-system fit (SSF; Rohrbaugh, Shoham, & Racioppo, 2002). For instance, Shoham et al (2007) showed that couples in which both partners smoked reported an increase in positive emotion when they were asked to smoke together in a laboratory setting, whereas those in single-smoker couples reported a decrease in positive emotion. Similarly, dual-smoker couples demonstrated an increase in emotional synchrony and engagement with each other, whereas single-smoker couples demonstrated the opposite (Butler, Hollenstein, Shoham, & Rohrbaugh, in press;Rohrbaugh et al, 2009).…”
Section: Eating To Regulate Emotions In Couplesmentioning
confidence: 95%
“…Previous studies on health-detrimental habits such as smoking have shown that, when such habits are shared by romantic partners, they may benefit the relationship, despite being related to worse health (Rohrbaugh, Shoham, Butler, Hasler, & Berman, 2009;Shoham, Butler, Rohrbaugh, & Trost, 2007). The pattern of an unhealthy behavior in some way benefitting the couple has been described in the literature as symptom-system fit (SSF; Rohrbaugh, Shoham, & Racioppo, 2002).…”
Section: Eating To Regulate Emotions In Couplesmentioning
confidence: 95%
“…6 On the one hand, a romantic partner who also smokes can be a risk factor for continued smoking. 6,9 On the other hand, the successful quitting of one partner seems to increase the likelihood of quitting in the other partner. 4 So far, the existing studies did not examine potential explaining mechanisms for why quitting smoking together might be more successful.…”
Section: Introductionmentioning
confidence: 99%
“…The latter studies show that single- and dual-smoker couples had very different experiences when someone actually smoked, based on measures of recalled positive and negative affect (Shoham et al, 2007), affective synchrony (Rohrbaugh et al, 2009), and linguistic markers of couple connectedness (Rohrbaugh et al, 2012). These differences may help to explain why smokers whose spouse or partner also smokes have a particularly hard time quitting and remaining abstinent.…”
Section: Old Wine New Bottlesmentioning
confidence: 99%
“…Participants in dual-smoker couples reported increased positive emotion contingent upon lighting up, while in single-smoker couples both partners (non-smokers and smokers alike) reported the opposite. Strikingly, changes in individual partners’ emotional experience from baseline to smoking depended almost entirely on a couple-level variable (partner smoking status), with no apparent contribution from a partner’s individual characteristics or even (in the case of single-smoker couples) whether he or she actually smoked during the assessment (Shoham, Butler, Rohrbaugh & Trost, 2007). …”
Section: Old Wine New Bottlesmentioning
confidence: 99%